Brooms are for Flying! - Rex, Michael (New York : Holt, 2000)
A group of young trick-or-treaters demonstrate that "feet are for stomping," "eyes are for peeking," "mouths are for moaning," and "tummies are for treating."
Accelerated Reader AR